Cu(ii)-Porphyrin based near-infrared molecules: synthesis, characterization and photovoltaic application. (8th January 2021) - Li, Renlong; Yuan, Yongqiang; Liang, Lei; Lu, Jianfeng; Cui, Cheng-Xing; Niu, Hongying; Wu, Zerun; Liu, Gongchu; Hu, Zhicheng; Xie, Ruihao; Huang, Fei; Zhang, Yuping
Abstract : Three novel Cu(ii )-porphyrin-based near-infrared non-fullerene acceptors were developed, which show strong intramolecular charge transfer absorption spectra. Abstract : Porphyrin and its derivatives play important roles in natural energy conversion applications. In this work, we designed and synthesized three novel acceptor–donor–acceptor (A–D–A) type small molecules (namely Por-Cu-IC, Por-Cu-ICF and Por-Cu-ICFF ) with the Cu(ii )-porphyrin as the central electron-donating core and fluorinated 2-(3-oxo-2, 3-dihydro-1 H -inden-1-ylidene)malononitrile as the electron-withdrawing end groups. These new molecules show broad absorption spectra from 300 to 900 nm with strong intramolecular charge transfer absorption spectra at around 800 nm, and an optical bandgap of about 1.4 eV. Organic solar cells (OSCs) based on these new molecules as non-fullerene electron acceptors achieved power conversion efficiencies from 0.5% to 2.44%. The OSCs were characterized by several techniques, including density functional theory (DFT), space-charge limited current (SCLC), photoluminescence spectra (PL) and atomic force microscopy (AFM). These results demonstrate a systematic study of Cu(ii )-porphyrin molecules, which could be used to design molecules for use in organic electronics.